Revitalisasi Pendidikan Akhlak Sebagai Fondasi Penguatan Moderasi Beragama Pada Generasi Z di Tengah Dinamika Digitalisasi - Achmad Fadil; Shendi Wahyu Safitri; Meisya Andini; Cintiyah Margaliani; Desti Umi Kalsum; Annisa Zahro; Cossin Alfatex (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to analyze the revitalization of moral education as a foundation for strengthening religious moderation among Generation Z amid the dynamics of digitalization. The rapid development of digital technology has significantly influenced the mindset, behavior, and character of the younger generation, both positively and negatively. Phenomena such as intolerance, hate speech, the spread of hoaxes, and the decline of communication ethics on social media indicate the importance of strengthening moral education in the lives of Generation Z. This study employs a qualitative approach using library research as its method. The research data were obtained from various literature sources, including books, scientific journals, research articles, and official documents related to moral education, religious moderation, Generation Z, and digitalization. The data analysis technique used was content analysis through the processes of data reduction, data presentation, and conclusion drawing. The results show that the revitalization of moral education plays an important role in shaping the character of Generation Z to become tolerant, wise, and capable of applying the values of religious moderation amid the development of digital technology. Moral education also functions as a means to strengthen tolerance, respect diversity, and prevent the growth of extremism and intolerance in the digital sphere.